Конституція України діє, конституційні перетворення тривають (до 15-ї річниці Конституції України) - Орзіх, Марко Пилипович; Єзеров, Альберт Анатолійович; Орзих, Марк Филиппович; Езеров, Альберт Анатольевич; Orzih, Mark; Ezerov, Al'bert (My University, 2011)
The adaption of the Constitution of Ukraine doesn't mark the end of the constitutional reform in the country. The constitutional reform still lasts because of the lack of defined by the science and practice tools of constitutional modernization and reformation. These tools are necessary to create the conditions for building the system of modern Ukrainian constitutionalism.
Орзіх М. П., Єзеров А. А. Конституція України діє, конституційні перетворення тривають (до 15-ї річниці Конституції України) / М. П. Орзіх, А. А. Єзеров // Наукові праці Національного університету «Одеська юридична академія». Т. 10 / голов. ред. С. В. Ківалов ; МОНмолодьспорт України, НУ "ОЮА". – Одеса : Юрид. л-ра, 2011. – C. 28-46.
Keywords: Конституція; конституційна модернізація; конституційне реформування; Конституційний Суд України; Конституция; конституционная модернизация; конституционное реформирование; Конституционный Суд Украины; Constitution; constitutional modernization; constitutional reform; The Constitutional Court of Ukraine